CARDIAC CT DIAGNOSTIC UTILITY IN THE ASSESSMENT OF BICUSPID AORTIC STENOSIS: A COMPARATIVE STUDY WITH ECHOCARDIOGRAPHY AND OPERATIONAL RESULTS - Kalsoom, F; MUSHTAQ , K; ZAFAR , U; TARIQ , S (Biological and Clinical Sciences Research Journal, 2022)
The bicuspid aortic valve is the most prevalent congenital cardiac abnormality, often leading to symptoms in middle-aged individuals. It is a significant determinant of aortic valve dysfunction in the young population. This study aimed to assess the diagnostic utility of cardiac CT in evaluating individuals with bicuspid aortic valve disease. Thirty consecutive individuals with aortic stenosis who underwent surgical valve repair from January 2021 to July 2022 at Chaudhary Pervez Ellahi Institute of Cardiology Multan, Pakistan, were included in the study. ECG-gated CT and echocardiography were performed utilising a 64-MDCT scanner. Imaging findings regarding the number of aortic valve leaflets (bicuspid or tricuspid) were compared with intraoperative observations. Statistical analysis was conducted using one-way univariate analysis of variance. The aortic valve area (AVA) was assessed using CT and echocardiography, and the results were statistically analysed using a paired Student’s t-test.: Eleven 30 patients had bicuspid aortic valves, while nineteen had tricuspid aortic valves. Echocardiography failed to determine the type of aortic valve in five patients due to severe calcification. The sensitivity, specificity, positive predictive value, and negative predictive value for detecting a bicuspid aortic valve were 75.5%, 60.3%, 67.6%, and 93.5%, respectively, for echocardiography, and 93.7%, 100%, 100%, and 96.7%, respectively, for CT. CT findings were not significantly different from perioperative observations (p = 0.87), while echocardiographic results were (p < 0.05). CT and echocardiography yielded AVA measurements of 0.931 ± 0.42 cm2 and 0.649 ± 0.241 cm2, respectively, with a significant difference (p < 0.05). ECG-gated cardiac CT provides a reliable morphologic diagnosis of bicuspid aortic stenosis, especially in individuals with significant valve calcification.